Mismatch repair gene MLH3 Pro844Leu and Thr942Ile polymorphisms and the susceptibility to cervical carcinoma and HPV infection: a case-control study in a Chinese population. - Feng Ye; Qi Cheng; Jiajie Shen; Caiyun Zhou; Huaizeng Chen (PLoS ONE)
To investigate the association between MLH3 Pro844Leu, Thr942Ile polymorphisms and potential linkage with the risk of cervical carcinoma and potential effect on protein function, we carried out a case-control study with 400 cervical squamous cell carcinoma, 400 CIN3 and 1200 normal controls in a Chinese population. The results showed that there was an increased risk of cervical carcinoma and CIN3 associated with the genotype 844CT [OR 2.17 (1.61-2.94); P<0.001; OR 1.49 (1.08-2.07), P 0.017, respectively] and a decreased risk with the 942CT genotype [OR 0.56 (0.38-0.82); P<0.001; OR 0.37 (0.24-0.58), P<0.001, respectively]. Most 844CT genotypes were linkage CT(844)-CC(942), which increased the risk of cervical carcinoma and CIN3 [77/83, OR 2.04 (1.48-2.80), P<0.001; 55/61, OR 1.46 (1.03-2.06), P 0.035, respectively]. Most 942CT were linkage CC(844)-CT(942), which decreased the risk of cervical carcinoma [29/35, OR 0.60 (0.40-0.91); P 0.017; 18/24, OR 0.33 (0.20-0.55), P<0.001, respectively]. In some grouping, the 844CT and 942CT were further enriched; especially HR-HPV-positive subjects both in the CIN3 and the cervical carcinoma, the 844CT had greater enrichment. These results included that CT(844)-CC(942) was associated with a high risk of cervical carcinoma and CIN3, and the CC(844)-CT(942) decreased the risk. The 844CT had a higher level of enrichment in HR-HPV positive individuals, which is probably related to HR-HPV susceptibility. There was no significant difference of the MLH3 mRNA expression and these two amino acid substitutions did not impact on the protein function.